Beef Production in the Southwestern United States: Strategies Toward Sustainability - Spiegal, Sheri; Cibils, Andres F.; Bestelmeyer, Brandon T.; Steiner, Jean L.; Estell, Richard E.; Archer, David W.; Auvermann, Brent W.; Bestelmeyer, Stephanie V.; Boucheron, Laura E.; Cao, Huiping; Cox, Andrew R.; Devlin, Daniel; et al. (Frontiers in Sustainable Food Systems, 2020)
From grazing lands to meat packing, beef production systems in the United States are striving to meet global demands without compromising environmental quality or local profitability. These challenges and opportunities are manifest in four US regions connected ecologically and socially through beef production: the American Southwest, the Ogallala Aquifer region, the Northern Plains, and the Upper Midwestern Corn Belt. Most calves raised on extensive, arid Southwestern ranches are exported to the Ogallala Aquifer region for finishing on grains that are grown either locally on Ogallala Aquifer water or imported from the Upper Midwest. Changes in climate, vegetation, and human demographics threaten the sustainability of the regionally-interconnected system. Heritage cattle genetics, precision ranching, and alternative supply chain options are three strategies that show promise for addressing these sustainability threats, but major knowledge gaps exist. For instance, while environmentally-friendly landscape use by Raramuri Criollo, a heritage cattle type, has been identified in several arid rangeland settings, little is known about their performance in conventional feed yards. While precision agriculture is already prevalent in croplands, less is known about how such technologies can be cost effective in arid rangelands. Moreover, many perceive grass-finishing on rangeland as environmentally friendly and beneficial for local agricultural communities, but tradeoffs involving greenhouse gas emissions, increased rangeland use, and disruption of cattle feeding systems of the Ogallala Aquifer region must be assessed. Here we introduce a USDA-NIFA Coordinated Agricultural Project designed to fill these knowledge gaps and advance sustainability of beef production linked to the US Southwest. With a boundary-spanning approach of education, participatory research, and extension, the project is identifying tradeoffs of the three strategies with explicit attention to pericoupling (i.e., socioeconomic and environmental interactions) of regions connected by beef production and full consideration of the coupled ecological and social systems within those regions.